Purification and Biophysical Properties of Acute Haemorrhagic Conjunctivitis Virus - Yamazaki, Shudo (1974)
The buoyant density of acute haemorrhagic conjunctivitis virions labeled with either [(3)H]uridine or [(3)H]leucine was 1.34 g/ml in CsCl and 1.25 g/ml in sucrose. RNA extracted from the virions gave a sedimentation coefficient of approximately 34S in sucrose, and was found to be sensitive to RNase. Molecular weight of RNA was calculated to be 2.5 × 10(6) using poliovirus RNA for reference.